Guidelines of the Italian Society of Videosurgery in Infancy for the minimally invasive treatment of the esophageal atresia - Salvatore Fabio Chiarenza; Maria Luisa Conighi; Ciro Esposito; Maria Escolino; Fabio Beretta; Maurizio Cheli; Vincenzo Di Benedetto; Maria Grazia Scuderi; Giovanni Casadio; Maurizio Marzaro; Leon Francesco Fascetti; Andrea Conforti; et al. (PAGEPress Publications, 2019)
Esophageal Atresia (EA) is defined as an interruption in esophageal continuity that results in a proximal tract that ends in a blind pouch in 98% of cases, and a distal tract that in 87% of cases arises via a Fistula from the Trachea (TEF). (...).